THE HOLIDAY OF KSANTIKA IN ANCIENT MACEDONIA (Philological Studies, 2019)
Ksanthika was a celebration of the army of the ancient Macedonians which was celebrated in ancient times. It was held in the spring, in the sixth month of the calendar of the ancient Macedonians Xandikos or March, according to our modern calendar. It functioned as a solemn rite of lustration. In essence it was a kind of a magical ritual purification of the army led by the King, in a particularly festive atmosphere, where the army passed between two halves of a sacrificed dog. In the parade, during the purification, the King was accompanied by the family, the hetairoi and the Macedonian army. After this an unusual mimetic game of fighting between the two warring sides followed. The text is an attempt to reconstruct the ancient Macedonian rite for which the data in the historical sources are few and fragmentary, on the one hand, but on the other hand inspirational for analysis and assumptions about the nature and meaning of this celebration and the customs tied to it.
Keywords: Ksanthika, rite of lustration, Macedonian army, dog sacrifice